The Impact of Globalization on Pancasila as a Human Rights-Based Ethical System in Indonesia - Putri Aulia Rahmi; Rahma Zakira; Akbar Kurnia (JUSTICES: Journal of Law, 2025)
In a globalized world, human rights have become an international political commodity that can be used by international institutions and foreign countries to influence the governance of a country. Moral decline occurs when external values dominate and lead to bad behavior such as low self-esteem. This process brings challenges and opportunities, such as cultural domination and economic inequality that affect the fulfillment of human rights. Political ethics is crucial in ensuring justice and respect for individual rights in the global era. International cooperation is needed to address human rights violations and encourage the implementation of universal principles in public policy. Therefore, the Indonesian government as part of the international community must create an ethical system that prioritizes the protection of human rights. As a result, human rights apply to every individual regardless of location and time. Such human rights are individual, essential, and sacred. It is also absolute, permanent, and indivisible, and is an indivisible right for humans Muhtaj, (2001: 23).